Psychometric Assessment of an Instrument Designed to Measure Work Life Balance - Hayman, Jeremy (School of Management, Curtin University of Technology, Perth, Western Australia and the Singapore Human Resources Institute, 2005)
Work family conflict and work life balance issues have received a great deal of attention from researchers and contemporary employers. Nevertheless, there is a lack of reported scales for assessing the construct of work life balance. This study evaluated a 15 item scale for assessing the construct of work life balance adapted from an instrument reported by Fisher-McAuley, Stanton, Jolton and Gavin (2001) with data obtained from 61 human resource administrators of a large university in Western Australia. Factor analysis confirmed a robust three factor solution. This paper reports and validates a new measure to capture employee perceptions of work life balance while discussing implications for human resource practitioners in the Asia Pacific region.